Carrier-envelope frequency stabilization of a Ti:sapphire oscillator using different pump lasers - Vernaleken, Andreas; Schmidt, Bernhard; Wolferstetter, Martin; Haensch, Theodor W.; Holzwarth, Ronald; Hommelhoff, Peter (Optics Express, 2012)
We investigate the suitability of various commercially available pump lasers for operation with a carrier-envelope offset frequency stabilized Ti:sapphire oscillator. Although the tested pump lasers differ in their setup and properties (e.g., single vs. multi-mode), we find that they are all well-suited for the purpose. The residual rms phase noise (integrated between 20Hz and 5MHz) of the stabilized oscillator is found to be below 160mrad with each pump laser, corresponding to less than 1/40 of an optical cycle. Differences in performance vary slightly. In particular, our results indicate that the latest generation of multi-mode pump lasers can be used for applications where precise phase control of the oscillator is strictly required. © 2012 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2012.nat.dphy.IAP.exphys.carrie